Design Principles for Considering the Participatory Relationship of Students, Teachers, Curriculum, and Place in Project-Based STEM Units - Jessica R. Stephenson Reaves; Rasheda Likely; Anna Maria Arias (MDPI AG, 2022)
Historically, STEM learning spaces and curriculum have overlooked the strengths and agency of students, teachers, and their communities. Project-based STEM units about environmental issues like water quality offer the possibility to create more expansive, equitable learning experiences. These units can leverage local problems and resources while also including the global dimensions of the issue to provide meaningful opportunities for diverse student sensemaking. However, even project-based STEM learning requires explicit attention to the agency of teachers, students, and place. In order to identify a set of design principles for supporting equitable learning in a project-based STEM curriculum, this manuscript brings together a set of empirical and theoretical frameworks including teacher participatory relationship with the curriculum, culturally sustaining pedagogy, critical pedagogy of place, and equitable sensemaking. The authors use these frameworks to describe a conceptual model of Participatory Relationship of Students, Communities, Teachers, Curriculum and Place. Then, the manuscript outlines a set of seven design principles that connect to the theoretical frameworks to the conceptual model and provide implementation strategies with examples of how we apply these design principles to a project-based STEM unit for 4-8 grade students. The design principles have implications for design of future project-based units and learning opportunities for teachers and students.